2018
DOI: 10.3389/fimmu.2018.00791
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanocapsules for Vaccine Delivery: Influence of the Polymeric Shell on the Interaction With the Immune System

Abstract: The use of biomaterials and nanosystems in antigen delivery has played a major role in the development of novel vaccine formulations in the last few decades. In an effort to gain a deeper understanding of the interactions between these systems and immunocompetent cells, we describe here a systematic in vitro and in vivo study on three types of polymeric nanocapsules (NCs). These carriers, which contained protamine (PR), polyarginine (PARG), or chitosan (CS) in the external shell, and their corresponding nanoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…Besides, they are muco- [ 27 ] and bioadhesive towards negatively charged biological membranes [ 28 ]. These NCs have been used as a drug delivery platform for insulin [ 29 ], flavonoids that interfere with bacterial quorum sensing [ 30 ], poorly water-soluble capsaicin [ 31 , 32 ], or vaccines [ 33 ]. Despite the fact that these NCs have consistently shown efficacy as drug delivery carriers, the precise mechanistic aspects that govern the interactions with the body and cellular fate upon being administered, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they are muco- [ 27 ] and bioadhesive towards negatively charged biological membranes [ 28 ]. These NCs have been used as a drug delivery platform for insulin [ 29 ], flavonoids that interfere with bacterial quorum sensing [ 30 ], poorly water-soluble capsaicin [ 31 , 32 ], or vaccines [ 33 ]. Despite the fact that these NCs have consistently shown efficacy as drug delivery carriers, the precise mechanistic aspects that govern the interactions with the body and cellular fate upon being administered, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they are muco- [21] and bioadhesive towards negatively charged biological membranes [22]. These NCs have been used as a drug delivery platform for insulin [23], flavonoids that interfere with bacterial quorum sensing [24], poorly water-soluble capsaicin [25,26], or vaccines [27]. Despite the fact that these NCs have consistently shown efficacy as drug delivery carriers, the precise mechanistic aspects that govern the interactions with the body and cellular fate upon being administered, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we hope that the formulation developed here has a high interaction with the immune system and that is shows adjuvant activity when it is administered in vivo. Finally, recent studies have shown that the polymeric shell in different types of nanocapsules can influence complement activation and immune system interactions and can also influence in vivo performance [ 48 ].…”
Section: Resultsmentioning
confidence: 99%